2009
DOI: 10.1128/iai.00439-09
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Binding Domain of Streptococcus oralis Glyceraldehyde-3-Phosphate Dehydrogenase for Porphyromonas gingivalis Major Fimbriae

Abstract: Porphyromonas gingivalis forms communities with antecedent oral biofilm constituent streptococci. P. gingivalis major fimbriae bind to glyceraldehyde-3-phosphate dehydrogenase (GAPDH) present on the streptococcal surface, and this interaction plays an important role in P. gingivalis colonization. This study identified the binding domain of Streptococcus oralis GAPDH for P. gingivalis fimbriae. S. oralis recombinant GAPDH (rGAPDH) was digested with lysyl endopeptidase. Cleaved fragments of rGAPDH were applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 34 publications
(31 reference statements)
0
31
0
Order By: Relevance
“…The GAPDH of the bacterium responsible for causing pneumonia and meningitis, Streptococcus pneumoniae, also acts as a plasminogen binding protein (24), which is important in the ability of this organism to cross endothelial and epithelial cell barriers (11). In Streptococcus agalactiae, GAPDH is reported to function as a virulence factor with B lymphocyte-modulatory activity (120), and the same enzyme from Streptococcus oralis binds to the major fimbriae of Porphyromonas gingivalis and appears to be important in the colonization of the latter organism (130). In Streptococcus suis serotype 2, the GAPDH enzyme functions as an albumin binding protein (147) and also as an adhesin for cell binding (28).…”
Section: Moonlighting Bacterial Glycolytic Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…The GAPDH of the bacterium responsible for causing pneumonia and meningitis, Streptococcus pneumoniae, also acts as a plasminogen binding protein (24), which is important in the ability of this organism to cross endothelial and epithelial cell barriers (11). In Streptococcus agalactiae, GAPDH is reported to function as a virulence factor with B lymphocyte-modulatory activity (120), and the same enzyme from Streptococcus oralis binds to the major fimbriae of Porphyromonas gingivalis and appears to be important in the colonization of the latter organism (130). In Streptococcus suis serotype 2, the GAPDH enzyme functions as an albumin binding protein (147) and also as an adhesin for cell binding (28).…”
Section: Moonlighting Bacterial Glycolytic Enzymesmentioning
confidence: 99%
“…For example, the number of 10-kDa (100-amino-acid residue) proteins that can, in theory, be produced is 20 100 or 10 130 . To put 10 130 in perspective, it is estimated that the number of stars in the universe is around 10 24 .…”
mentioning
confidence: 99%
“…The plasmid pQE30-Sogap, expressing S. oralis recombinant His-tagged GAPDH (HTrGAPDH), was prepared as described previously (22). A mutation in the P. gingivalis FimA fimbria binding domain of rGAPDH [residues 166 to 183; termed rGAPDH(⌬166-183)] was introduced into pQE30-Sogap using the primers Sogapdh⌬166-183F and Sogapdh⌬166-183R (Table 1).…”
Section: Purification Of S Oralis Rgapdh(⌬166-183)mentioning
confidence: 99%
“…However, multiple functions have been reported recently for GAPDH, including roles in membrane fusion, microtubule binding, phosphotransferase activity, nuclear RNA export, DNA replication and repair, apoptosis, and viral pathogenesis (20,21). Our previous study demonstrated that the P. gingivalis FimA fimbria binding domain in S. oralis ATCC 9811 GAPDH was within amino acid residues 166 to 183, and that the peptide corresponding to this domain (DNFGVVEGLMTTIHAYTG) exhibited strong binding activity toward recombinant FimA fimbriae (rFimA) by BIAcore analysis (K A ϭ 4.51 ϫ 10 7 M Ϫ1 ) (22). The synthetic peptide inhibited biofilm formation between various streptococci and P. gingivalis strains with different types of FimA fimbriae in a dose-dependent manner.…”
mentioning
confidence: 99%
“…Besides their glycolytic activity in the cytosol, these enzymes have been found at the surface of micro-organisms, where they act as binding partners of proteins of the human Abbreviations: ECM, extracellular matrix; FCS, fetal calf serum; GAPDH, glyceraldehyde-3-phosphate dehydrogenase; MMR, multiple mutation reaction. Microbiology (2011Microbiology ( ), 157, 2328 As a surface-associated protein, GAPDH can interact with not only one or more specified host factors like fibronectin, fibrinogen, albumin, laminin, collagen and plasminogen but also human colonic mucin, human epithelial and endothelial cells or fimbriae of other bacterial species in biofilms (Pancholi & Fischetti, 1992;Gozalbo et al, 1998;Bergmann et al, 2004;Barbosa et al, 2006;Egea et al, 2007;Kinoshita et al, 2008;Nagata et al, 2009;Purves et al, 2010;Tunio et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%